Near-Fault Ground Motion Influence on the Seismic Responses of a Structure with Viscous Dampers considering SSI Effect - Jinping Yang; Peizhen Li; Hang Jing; Meng Gao (Advances in Civil Engineering)
This paper studies the influence of the characteristics of the near-fault ground motion on the seismic responses of the structure with energy dissipation devices including soil-structure interaction (SSI). A ten-story reinforced concrete frame rested on soft site is introduced, and the viscous dampers added in the frame are designed. The numerical analysis method of the soil-structure system with viscous dampers is established through ANSYS program. In addition, the response spectra of the main characteristics of the near-fault ground motion, like hanging wall effect, velocity pulse-like effect, and forward-directivity effect, are investigated carefully to learn the features of spectra energy distribution. And then, the dynamic time-history analysis is performed on the SSI system with and without viscous dampers subjected to the selected near-fault ground motion. The study reveals that the seismic responses of the structure subjected to near-fault ground motion with hanging wall effect are obviously larger than those of the footwall effect, indicating the distinct hanging wall effects on the structural dynamic responses. In addition, the performance of the structure with viscous dampers is more influenced by the ground motion containing fling-step effect than that with forward-directivity effect. Moreover, the influence of the horizontal component of forward-directivity ground motion on the seismic responses of the structure is more obvious than that of parallel component ground motion. Consequently, the hanging wall effect, velocity pulse, and horizontal component in forward-directivity effect of the near-fault ground motion have distinct influence on the seismic responses of the structure with energy dissipation devices considering SSI effect, providing insight towards the performance-based seismic design of buildings rested at the near-fault sites considering the seismic SSI effect.